Trends in prevalence and survival of very low birthweight infants, England and Wales: 1983-7. Issue 11 (November 1991) - Alberman, E; Botting, B
Abstract : Between 1983 and 1987 over 99% of all infants born in England and Wales had their birth weights recorded when the birth was registered. Trends in occurrence and one year survival of those who weighed under 1500 g at birth have been calculated in 100 g groups, separately for single and multiple births. By 1987 singleton live births in England and Wales who weighed between 700 and 799 g had a 43% chance of surviving to 1 year compared with a 32% chance five years earlier; those who weighed 800 to 899 g had a 55% chance compared with 46%. The absolute number of survivors weighing between 500 and 999 g at birth increased by nearly 50% between 1983 and 1987, and there was a 30% increase overall in survivors weighing less than 1500 g.